Pengembangan dan Evaluasi Kurikulum Pendidikan Di Pondok Pesantren Desa Ganjaran Gondanglegi Malang - Yazidul Busthomi; Syamsul A’dlom (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Islamic boarding schools in the village of Malang Ganjara n Gondanglegi are Islamic educational institutions with a Salaf Islamic curriculum so far believed to be a place of religious education, proven to be one of the places where preaching education still exists. However, curriculum development and evaluation i n this Islamic boarding school, there is still no data that can be ascertained, so it is interesting to study. So the researcher raised a title